Victim–offender trajectories: explaining propensity differences from childhood to adulthood through risk and protective factors - DeCamp, Whitney (The British journal of criminology, 2018)
Although extensive evidence supports a relationship between victimization and offending, research has been limited in focusing on this association during only a brief period in the life course. Existing research has not adequately considered the influence of early-onset problem behaviours on victimization and offending later in life. This study advances the literature by examining propensities for violent victimization and offending and whether differences in these trajectories can be explained by early-onset problem behaviour. Using longitudinal data from the Offending, Crime and Justice Survey, simultaneous group-based trajectory modelling of violent victimization and offending is performed to examine the overlap in trajectories for these two outcomes, with additional analyses estimating the effects from various predictors on trajectory membership. Results indicate significant correlations between victimization and offending trajectories. Deviant lifestyles, particularly substance use in the early life course and property offending, play a pivotal role in enhancing risk for both victimization and offending.